Valorization of Taioba Products and By-Products: Focusing on Starch - Samanta de Paula de Almeida Duarte; Bárbara E. Teixeira-Costa; Rosely Carvalho do Rosário; Edna Regina Amante; Márlia Barbosa Pires; Orquídea Vasconcelo dos Santos (Foods, 2024)
Unconventional food plants, popularized in Brazil as PANC, remain underutilized globally. In that sense, this study aims to explore the nutritional and functional properties of taioba (Xanthosoma sagittifolium), a plant with edible leaves and tubers, and to investigate its potential for industrial-scale application as a source of starch. A systematic review was carried out and meta-analysis following the PRISMA guidelines was conducted based on a random effects synthesis of multivariable-adjusted relative risks (RRs). The searches were carried out in seven search sources, among which were Web of Science, Elsevier’s Science Direct, Wiley Online Library, Springer Nature, Taylor & Francis, Hindawi, Scielo, ACS—American Chemical Society, and Google Scholar. The systematic review was guided by a systematic review protocol based on the POT strategy (Population, Outcome, and Types of studies), adapted for use in this research. Mendeley was a resource used for organization, to manage references, and to exclude duplicates of studies selected for review. The findings revealed that taioba leaves are abundant in essential nutrients, proteins, vitamins, and minerals. Additionally, the tubers offer rich starch content along with vitamins and minerals like iron, potassium, and calcium, making them an ideal substitute for conventional sources on an industrial scale. This research highlights the significance of studying the functionalities, applicability, and integration of this PANC in our diets, while also emphasizing its capability as a substitute for traditional starch varieties. Moreover, exploiting this plant’s potential adds value to Amazonian resources, reduces import costs, and diversifies resource utilization across multiple industrial sectors.